FUNGI, INCLUDING FUSARIUM SPP., ON EARS OF CONVENTIONALLY AND ECOLOGICALLY GROWN WINTER WHEAT - Martyniuk, S.; Oroń, J.; Kozieł, M. (Plant Breeding and Seed Science, 2011)
Ears of winter wheat cultivars (Bogatka and Legenda) grown under conventional and ecological (organic) farming systems, were sampled at different developmental stages and examined for their colonization by filamentous fungi, including Fusarium spp. Ears samples were shaken in sterile water containing 0.01% of Tween 80 and appropriate 10-fold dilutions of the initial suspension were inoculated onto agar medium containing antibiotics to inhibit bacterial contaminants. After 6-7 days of incubation at 28o C fungal colonies were counted and after further 4 days fragments of colonies were transferred onto other media for identification. On ears at flowering no Fusarium species were found in 2008 with dry and hot July, but in 2009 with more frequent rainfalls in July Fusarium poae, F. tricinctum and F. avenaceum were detected on winter wheat ears at the flowering stage. At the hard kernel stage the following species were isolated from winter wheat ears: F. poae and F. sporotrichioides in 2008 (17 and 18 isolates respectively) and F. avenacum, F. crookwellense, F. poae, F. sporotrichioides and F. tricinctum in 2009 (2, 18, 39, 2 and 17 isolates respectively, and 9 unidentified Fusarium). In 2008 more Fusarium spp. were found on winter wheat ears grown under the conventional system than under the ecological (organic) system. In the ecological system wheat stands are thinner but taller (due to the lack of any mineral fertilizers and plant growth regulators) and in consequence winter wheat ears in this system may keep moisture shorter than those in the conventional system. It seems that this difference may be the most important factor influencing colonization of winter wheat ears by Fusarium spp. and other fungi under the compared farming systems.